POLA PENGEMBANGAN KURIKULUM PAI DI MADRASAH MELALUI PENDEKATAN KOMPREHENSIF - hasan, hafiedh; Putri, Ayu Eka (Kopertais Wilayah X Jawa Tengah, 2020)
The curriculum that is developed by the Islamic based school/Madrasah is an operational curriculum that is compiled and implemented by each school/Madrasah and it is used as a reference for learning in school. The urgency of the attention and application of the principle is to ensure that the Islamic education curriculum is developed completely convenient with the condition of the students, schools, communities so that it does not only revolve around the issue of aqidah and morality but also includes all the sciences that relate to various aspects of human life, balanced between the worldly needs and the hereafter needs, body and soul, material and spiritual. The new paradigm of Islamic Education requires integrated and continuous innovation. One manifestation is an innovation by the teacher in learning activities. The teacher's habit of gathering information about students' level of understanding through questions, observations, assignments, and tests will be very useful in determining the level of student mastery and in evaluating the effectiveness of the learning process.